The impact of change in the definition of bank capital according to Basel 3 - Odada, Lameck Onyango (Department of Finance and Tax, 2016)
The objective of this study is to analyse the impact of the change in the definition of bank capital according to Basel 3. The 2008 financial crisis exposed the flaws in the global regulatory and supervision framework and also showed that Basel 2 could not fully protect against bank failures. In order to address the gaps, loopholes and deficiencies of Basel 2 and to guard against any future crises, the Basel 3 accord was implemented in 2013. The key change introduced by Basel 3 is the requirement that banks hold more capital. However, the Basel 3 accord also changed the definition of bank capital and the definition of risk-weighted assets (RWAs). In comparing Basel 2 with Basel 3, several changes in the definition of capital appear. It is therefore important to analyse the impact of the capital definition change introduced in Basel 3 excluding the changes in the definition of RWAs. The study used a sample of the fifty largest commercial and investment banks by asset size from the USA and the Europe region. The study calculated the Basel 2 Tier 1 capital ratio and Basel 3 Tier 1 capital ratio at the same point in time by only changing the reported capital under Basel 2 and Basel 3 but keeping the RWAs the same at Basel 2 level. This is to isolate the capital definition change and exclude changes to the RWAs definition. The change in the regulatory Tier 1 capital ratio is the estimated impact of the change in the definition of bank capital according to Basel 3. The data sample shows that the banks in the Europe region are larger in size than the USA banks on average. The results show that the change in the Basel 3 capital definition had a positive impact on the European banks' capital ratios and in contrast there was a negative impact on the USA banks' capital ratios. The limitations of the study include the use of a small sample size of fifty banks, the omission of Asian banks from the sample size even though these include some of the largest banks in the world, and the selection of banks with December year ends only. This study contributes to the literature because it is the first study to examine the capital definition change in Basel 3.